Despite various initiatives thus far can there be sustainable development for humanity? - Dokun Oyeshola (Global Journal of Ecology - Peertechz Publications, 2020)
There are varieties of efforts to arrest the challenges of environmental degradation and promote sustainable development at the domestic and global levels. These efforts are carried out within the context of international politics with its core values of national interest ideology, democracy and liberalism. The outcome of the efforts is still very far from the objectives and goals of sustainable development judging from the global reality where some human activities are still contributing immensely to the polluted land, air and water leading to climate change and consequent challenges to the carrying capacity of the Planet. Within the international system, it has been observed that there are two major arbitrary systems that are vying for control of the world. These are the soft totalitarianism of secularism and the hard totalitarianism of Islam. It is in this light of the above observations that I am particularly interested in asking the question that despite various initiatives on ground thus far and the ones to be designed, can there be sustainable development for humanity?.